Ecophysiological characteristics of key members of Betaproteobacteria in freshwater bacterioplankton - Kasalický, Vojtěch (Jihočeská univerzita, 2012)
This thesis primarily focuses on one segment of freshwater Betaproteobacteria, the Limnohabitans genus (including the RBT lineage). As opposed to other recent research directions, the major aim was to recover the members of the previously uncultured RBT lineage through their isolation from various freshwater habitats. However, the results presented in this thesis have also ambitions to go far beyond the taxonomic descriptions only; the dissertation intends to contribute significantly to unveiling of important ecophysiological characteristics of the studied lineage in a set of both laboratory and field research. Therefore, understanding of growth characteristics, mortality, diversity and life strategies of aquatic microbes is of highest importance regarding profound human impact on water quality and increasing need of drinking water supplies.
Ecophysiological characteristics of key members of Betaproteobacteria in freshwater bacterioplankton
Keywords: vodní; ekofyziologie; bakterie; Limnohabitans; Betaproteobacteria; predace; izolace; diverzita; aquatic; ecophysiology; microbial; bacteria; Limnohabitans; Betaproteobacteria; predation; isolation; microdiversity